TQM in business education in Malaysia : a case study based on the application of nominal group technique / Nor Azian Khairuddin and Rafikul Islam - Khairuddin, Nor Azian; Islam, Rafikul (Faculty of Business and Management ; UiTM Press, 2000)
There is growing concern about the capabilities and competencies of the graduates produced by our institutions of higher learning. Higher learning institutions must respond to the challenges faced by business community by providing graduates competent in all important aspects or performance to meet the expectations of the employers. The present paper in intended to assist Ungku Omar Polytechnic, Malaysia, to meet the challenges it is facing. The major objective of this paper is to present a report of gathering, analyzing and interpreting the views of various stakeholders, namely, students, lectures and administrators regarding how to improve teaching and learning effectiveness at the Commerce Department, Ungku Omar Polytechnic.